PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PROBLEM BASED LEARNING MATERI PROGRAM LINEAR UNTUK SISWA KELAS XI SMA/MA - Saputri, Maya; Armis, Armis; Roza, Yenita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is a development research which aims to producemathematics learning tools. The resulting learning devices in the form of syllabus,lesson plan (RPP) and student activity sheet (LAS) based on Problem Based Learning on linear program material for grade XI senior high school students. The development model used is the 4-D model which consists of the Define, Design, Develop, and Disseminate stages. Data collection instruments used in this study were validation sheets and student response questionnaires. The learning tools developed were validated by three validators and revised based on validator’s suggestion, and studentactivity sheet evaluated by three high school students to see the readability of student activity sheet. The average percentage of validation result for Syllabus is 95.83%, lesson plan (RPP) 96.09%, and student activity sheet (LAS) 95.63%, so the learning tools are categorized as very valid. Then, a small group trial were conducted of the student activity sheeet which was developed on six students of SMA Negeri 1 Bukit Batu. The average practicaly percentage for student activity sheet is 86.25% with a verypractical category. Based on the results of data analysis, it is concluded that the mathematics learning device developed has met the valid and practical criteria for using by class XI senior high school students.Key Words: Mathematics Learning Tools, Problem Based Learning Model, Linear Program, 4-D Development Model